2021
DOI: 10.1111/jcpt.13528
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic‐pituitary‐gonadal axis and sexual functioning in metformin‐treated men after discontinuation of testosterone replacement therapy: A pilot study

Abstract: What is known and objective: Metformin was found to reduce elevated gonadotropin levels. The aim of the present study was to determine whether metformin modulates the impact of discontinuation of testosterone therapy on hypothalamic-pituitarygonadal axis activity and sexual function in men with low testosterone levels. Methods:The study included 28 men with late-onset hypogonadism (defined according to the criteria of the European Male Aging Study group) receiving testosterone undecanoate (120 mg in three equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…On the other hand, the LE8 encompasses four health factors: body mass index, blood lipids, blood sugar, and blood pressure. Hypogonadism frequently accompanies metabolic complications like obesity and diabetes; a reduction or absence of testosterone can precipitate metabolic disorders by elevating visceral lipids and worsening insulin resistance ( 34 , 35 ). Furthermore, the interplay between hypogonadism and metabolic disorders is recognized as bidirectional, affecting both functional and delayed forms of hypogonadism ( 29 ); Hyperglycemia can directly trigger a reduction in testosterone synthesis within Leydig cells by activating the TLR4-mediated oxidative stress pathway ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the LE8 encompasses four health factors: body mass index, blood lipids, blood sugar, and blood pressure. Hypogonadism frequently accompanies metabolic complications like obesity and diabetes; a reduction or absence of testosterone can precipitate metabolic disorders by elevating visceral lipids and worsening insulin resistance ( 34 , 35 ). Furthermore, the interplay between hypogonadism and metabolic disorders is recognized as bidirectional, affecting both functional and delayed forms of hypogonadism ( 29 ); Hyperglycemia can directly trigger a reduction in testosterone synthesis within Leydig cells by activating the TLR4-mediated oxidative stress pathway ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Souteiro et al (11) found IR is the primary risk factor of low testosterone levels in obese men, and some males with testosterone deficiency even have a higher IR index than patients with mild diabetes. Another pilot study found that Metformin, a diabetes drug, can restore the testosterone level of male patients with type II diabetes through improved IR (12). On the other hand, the decrease or deficiency of testosterone may lead to the development of metabolic disorders through increased visceral lipids and insulin resistance (13).…”
Section: Introductionmentioning
confidence: 99%